Pengaruh Kedisiplinan Kerja Karyawan Produksi Jasa Cuci Sepatu “Shoes Clearance Project” Kel. Nagasari Kab. Karawang - Ahmad Riatna Sandika; Enjang Suherman (CV. ITTC INDONESIA, 2024)
The results of the article show that the role of leadership is very influential on employee discipline in an effort to increase the productivity of MSMEs built on the shoe cleaning service project. In building employee discipline, the boss or leader must always be firm and take part in making existing decisions. If the boss is not firm and does not act fairly towards his employees, the employees will experience a decline in performance so that discipline is not maintained within the business premises. In an effort to discipline the employees, the boss takes aspects of the work environment and employees such as not being late so they arrive on time, motivating the workers so that productivity increases so that the business can develop, and ordering the workers to comply with the regulations that have been made at the place of business. The purpose of the article This is to increase insight into how to wash shoes and discipline employees at the